Growing urbanization : challenges and strategies - Sai Sujatha, D. (Discovery Publishing House Pvt. Ltd., 2012)
India has to improve its urban areas to achieve objectives of economic development. Keeping in view of the vital importance of Growing urbanization and its effects on basic amenities, an attempt has been made to compile the papers presented in the National Seminar on "Growing Urbanization: Challenges and Strategies" by the academicians of different universities and institutions, to examine the various challenges and to assess the strategies to provide basic amenities on par with growing urbanization.